Contemporary Art. (Knokke : Andre Simoens Gallery)
Alechinsky, Pierre ; Appel, Karel ; Botero, Fernando ; Christo ; Davie, Alan ; dubuffet, Jean ; Fontana, Lucio ; Gilbert & George ; Jorn, Asger ; Lanskoy, Andrei ; LeWitt, Sol ; Mathieu, Georges ; Noland, Kenneth ; Pomodoro, Arnaldo ; Takis, Vassilakis ; Wyckaert, Maurice
boek